A critical analysis of the International Baccalaureate's Middle Years Programme assessment design with particular focus on feedback. (December 2014) - Hughes, Conrad
The International Baccalaureate's Middle Years Programme (IBMYP) is designed to support the development of creativity, critical thinking, international-mindedness and values. However, close inspection of the programme's assessment structure suggests that many of the competence-related and dispositional elements of the programme's construct are to be assessed using performance rather than competence models. The article discusses and problematises this tension. Furthermore, the salient formative assessment strategy of feedback, widely researched and accepted as a teaching technique with considerable gains for learning, is not sufficiently explained or developed in the IBMYP assessment guide to allow for deep understanding of its potential to move learning forward. The article argues for a more competence-related assessment design in the IBMYP with greater detail around the strategy of feedback for learning.